2016
DOI: 10.1186/s40249-016-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of leprosy in Malawi. Making the final push towards eradication: a clinical and public health perspective

Abstract: Statistically speaking, Malawi has achieved the World Health Organisation's target for the elimination of leprosy (<1 case per 10 000 people), yet the disease is still considered a leading cause of long term physical disability. In this case study the authors discuss the presentation of a 39-year-old gentleman to a district hospital in Malawi with multibacillary, lepromatous leprosy. The condition was initially managed in the community as an 'allergy' which suggests that local barriers currently hinder the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…As the study reveals nine in 10 peoples earn less than $1/day which indicates the possibility of the association of leprosy and poverty in Ethiopia. Although it is very difficult to demonstrate the link between poverty and leprosy at community or individual level, several epidemiological studies have consistently reported the strong association between leprosy and poverty at community and household level in Indonesia [13] in Bangladesh [14], in Malawi [15] and in India [16].…”
Section: Discussionmentioning
confidence: 99%
“…As the study reveals nine in 10 peoples earn less than $1/day which indicates the possibility of the association of leprosy and poverty in Ethiopia. Although it is very difficult to demonstrate the link between poverty and leprosy at community or individual level, several epidemiological studies have consistently reported the strong association between leprosy and poverty at community and household level in Indonesia [13] in Bangladesh [14], in Malawi [15] and in India [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pericytes are identifiable by a multitude of molecular markers, including neural-glial antigen 2 (NG2), beta-type platelet-derived growth factor receptor (PDGFRβ), CD146, G protein signaling 5 (RGS5), nestin, α-SMA, desmin, CD13, and alkaline phosphatase (AP) [ 46 , 115 , 116 ]. However, employing multiple markers remains essential as these markers are not exclusive to pericytes, and their use is needed to purify pericyte populations from specific organs [ 117 , 118 ]. Within skeletal muscles, pericytes are dividable into two primary subtypes based on the cellular marker expression: type I (PDGFRβ + NG2 + CD146 + and Nestin − ) and type II (PDGFRβ + NG2 + CD146 + and Nestin + ) [ 119 ].…”
Section: Pericytesmentioning
confidence: 99%
“…A instituição de EPS para profissionais, em especial da atenção primária, para a prevenção e controle da hanseníase, se constitui num potencializador do processo de trabalho em saúde, viabilizando ações eficazes na abordagem da hanseníase, desde o diagnóstico até a implementação de ações educativas, favorecendo a quebra da cadeia de transmissão, o autocuidado, a adesão ao tratamento, consequentemente, prevenindo complicações [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Biopolítica, vigilância de contatos e inclusão da família: desafios ao processo educativo…”
Section: Produção De Conhecimento E Gerenciamento Do Processo De Trab...unclassified